UJI INTEGRASI DAN CONTAGION EFFECT PASAR MODAL PADA LIMA NEGARA ASEAN (RISET EMPIRIS PASCA TERJADINYA KRISIS SUBPRIME MORTGAGE DAN KRISIS YUNANI) - Tarsisius Renald Suganda; Yonatan Soetrisno (University of Merdeka Malang, 2016)
Financial market comovement in ASEAN main member countries is still attractive to scrunitized, because this area is vulnerable to the impact on a global economic event. This study examined capital market integration of five ASEAN main members (Indonesia, Singapore, Malaysia, Philippines, and Thailand) by using September 200830 April 2013 data period. This period will divided into the post 2008 Subprime Mortgage crisis period and the post 2010 Greece crisis period. Vector Autoregressive (VAR) was used to test the comovement occurance among these capital markets and Granger Causality Test was used to analyze the contagion effect among these capital markets. The finding shows that the comovement was occurred among Indonesia, Malay-sia, Singapore and Thailands capital market during September 2008 to 30 April 2013 period. The comovement was still occured after 2008 Subpime Mortgage crisis period and 2010 Greece crisis period, although there is country namely Philippines which did not have the comovement at all against the other countries. Further-more, the finding shows that Indonesia capital market gives contagion effect to other ASEAN countries after 2008 Subprime Mortgage crisis and Greece financial crisis.